Identifying the needs of reticent pre-service English teachers for remediation course development - Soo, Ruey Shing; H. S., Goh (2020)
The development of any intervention to remedy student reticence should be based on students’ real needs. This is to avoid the risk of making generalisation and hasty decision in designing course contents. This study investigated reticent pre-service English teachers’ needs with the view of developing a remedial course to alleviate reticent behaviour and to improve oral participation in English for Academic Purposes classrooms. Adopting a mixed-methods approach, this study employed a survey, a semi-structured interview and a focus group discussion to collect data from pre-service English teachers and English instructors in a Malaysian state university. The findings revealed that the pre-service English teachers’ reticent behaviour was caused by virtual of their negative beliefs towards oral participation, lack of discussion skills and fear of negative evaluation. Additionally, the findings also implied that training in oral participation skills alongside relevant linguistic knowledge is needed for remediation of reticence as the reticent pre-service teachers encountered difficulties in asking questions, contributing ideas and providing connected utterances during open-class discussions. This study highlights the needs for further research in this domain in order to inform the development of intervention to remedy student reticence.